Water-Energy Nexus Dilemma for Hydrogen Production in Water-Scarce Regions - Aiman Albatayneh; Murad Al-Omary; Mustafa Jaradat; Mathhar Bdour; Yaqoub Al-Khasawneh; Muna Hindiyeh; Rafat Aljarrah (Energy Nexus, 2025)
Green hydrogen is increasingly recognized as a pivotal energy carrier that supports global decarbonization efforts and enables transitions to clean and sustainable energy systems. However, in water-scarce regions, the water-intensive nature of hydrogen production presents a significant dilemma within the water-energy nexus. This research investigates the challenges of meeting ambitious hydrogen production targets in Arab countries, where renewable freshwater resources are limited and already under strain. Using quantitative analyses, we reveal stark disparities among nations: In 2030, the percentage of renewable freshwater used for hydrogen production is minimal for Egypt and Morocco at <1 %, while Jordan, Oman, and Saudi Arabia face moderate usage at 1.58 %, 1.79 %, and 3.02 %, respectively, with the UAE reaching 16.67 %. By 2050, these percentages will escalate, with Egypt and Morocco still under 1 %. However, Jordan rises to 12.53 %, Oman to 21.25 %, Saudi Arabia to 17.50 %, and the UAE surges to an unsustainable 350 %, emphasizing the growing water challenges over time and highlighting the unsustainable reliance on freshwater in arid regions. This unsustainable reliance on freshwater intensifies competition with agriculture, domestic use, and other critical sectors, raising ethical concerns about resource allocation. The study proposes solutions to address these challenges, including using desalinated seawater, treated wastewater, brackish water, advanced electrolysis technologies, and water-efficient practices, combined with regional cooperation and policy innovations; these strategies can help balance hydrogen ambitions with sustainable water management in arid regions.